Upaya Siswa dalam Menyelesaikan Soal Matematika dengan Metode Pemecahan Masalah di Era Pandemi Covid-19 di SD Negeri 60 Banda Aceh - Tri Putri Utami; Indah Suryawati (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2022)
The purpose of this research is to find out the students' efforts in solving math problems with problem solving methods in the Covid-19 Pandemic Era at SD Negeri 60 Banda Aceh. The approach in this study uses a qualitative approach with the type of descriptive research. The subjects in this study were 5 fourth grade students consisting of 2 boys and 3 girls at SD Negeri 60 Banda Aceh. The inability of students to solve problems as above is influenced by the low ability of students to solve mathematical problems. Students are not able to analyze what is known from a question, students are also unable to identify the question of the question and cannot determine the steps that can be taken from the problem. Data collection techniques using problem solving problems, problem solving assessment criteria, interviews, documentation. The data were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the efforts made in solving the problem consisted of several steps. The first step begins with reading and understanding the questions, finding the information contained in the questions and determining the questions from the questions. Students also solve the problem by including the steps of completion or the formula used in order to get the right answer. The last step that students take before submitting the answer sheet to the teacher is to re-examine the answers to the math problems to make sure there are no erroneous data.